La técnica “Análisis de imágenes fijas” y su influencia en la producción de textos narrativos en el área de comunicación de los educandos del V ciclo de Educación en la I.E José Carlos Mariátegui - Herrera Pintado, Yovanny (2011)
The put a title to investigation " The technique analysis of fixed images and your influence in the production of narrativa texts in the area of communication in the pupils of the V the educational experimental institution's cycle of primary education José Carlos Mariátegui FEH study learning in the pupils considerad for the present - R/UNSM, sector Rupacucha, district of Rioja 2009 ", it happened because in this I.E. they observad difficulties in the production of narrativa texts, insinuating true difficulties in the process of teaching evidently. In this sense, and on the basis of the investigations that they preceded to this letter, it ran for candidata that if the technique related with the analysis of fixed images is applicable, then this will have influence significantly improving the production of narrativa texts in pupils, which constituted the fact-finding hypothesis. In order to determine the aforementioned influence, it was necessary to apply a pre and after proof, each constituted for 1 O items related to an image to measure the production of narrativa texts. In the oparating part, invastigatíon was driven undar a pre-experímenial design considering a very group conformad by 15 pupíls whích constituted the sign for present investigation. As to the results, the hypothesis was contrastad by maans of proof t Student for the difference paired off with a reliable level for the 95 %'s expariment, turning out well to demonstrate than the · application of the technique analysis of fixed images, has influenced the production of narrativa taxts evaluated in tha pupils significantly of the V Educación's cycla Primary of the Educational Experimental lnstitution José Carlos Mariátegui FEH-R/UNSM, Sector Rupacucha, district of Rioja.